Size effect tests of stocky reinforced concrete columns confined by stirrups. (5th April 2017) - Du, Min; Jin, Liu; Du, Xiuli; Li, Dong
Abstract : The paper deals with an experimental investigation of stocky reinforced concrete (RC) columns confined by stirrups with a slenderness ratio of 3. A total of 24 columns were designed and tested. In the tests, the confining action and the size effect for the columns with circular and square cross sections were studied, and the effects of stirrup ratio and concrete cover were also explored. The maximum structural sizes for the circular and squared columns were respectively 576 mm in diameter and 600 mm in cross‐sectional width. The test observations indicate that, increasing the stirrup ratio could make the enhancement of the nominal strength and improvement of ductility capacity. At the same stirrup ratios and cross‐sectional sizes, both the nominal strength of the circular columns is higher and thedeformation capacity is larger than those of the square columns. Overall, the failure of the RC columns with a lower stirrup ratio, without cover and having square cross section is more brittle, exhibiting a stronger size effect. In addition, the nominal compressive strengths of all the tested columns are in good agreement with the size effect law (SEL) proposed by Bažant.